Monofloral Corn Poppy Bee-Collected Pollen—A Detailed Insight into Its Phytochemical Composition and Antioxidant Properties - Aleksandar Ž. Kostić; Danijel D. Milinčić; Bojana Špirović Trifunović; Nebojša Nedić; Uroš M. Gašić; Živoslav Lj. Tešić; Sladjana P. Stanojević; Mirjana B. Pešić (Antioxidants, 2023)
The aim of this study was to compile a detailed phytochemical profile and assess the antioxidant properties of bee-collected pollen (PBP) obtained from corn poppy (Papaver rhoeas L.) plants. To achieve this, a lipid fraction was prepared for quantifying fatty acids using GC-FID. Extractable and alkaline-hydrolysable PBP fractions (obtained from a defatted sample) were used to determine the qualitative and quantitative profiles of phenolic compounds, phenylamides and alkaloids using UHPLC/Q-ToF-MS. Additionally, various spectrophotometric assays (TAC, FRP, CUPRAC, DPPH⦁) were conducted to evaluate the antioxidant properties. Phenolic compounds were more present in the extractable fraction than in the alkaline-hydrolysable fraction. Luteolin was the predominant compound in the extractable fraction, followed by tricetin and various derivatives of kaempferol. This study presents one of the first reports on the quantification of tricetin aglycone outside the Myrtaceae plant family. The alkaline-hydrolysable fraction exhibited a different phenolic profile, with a significantly lower amount of phenolics. Kaempferol/derivatives, specific compounds like ferulic and 5-carboxyvanillic acids, and (epi)catechin 3-O-gallate were the predominant compounds in this fraction. Regarding phenylamides, the extractable fraction demonstrated a diverse range of these bioactive compounds, with a notable abundance of different spermine derivatives. In contrast, the hydrolysable fraction contained six spermine derivatives and one spermidine derivative. The examined fractions also revealed the presence of seventeen different alkaloids, belonging to the benzylisoquinoline, berberine and isoquinoline classes. The fatty-acid profile confirmed the prevalence of unsaturated fatty acids. Furthermore, both fractions exhibited significant antioxidant activity, with the extractable fraction showing particularly high activity. Among the assays conducted, the CUPRAC assay highlighted the exceptional ability of PBP’s bioactive compounds to reduce cupric ions.